The (Un)Sustainability of Higher Education Institutions in Jordan - Hassan, Sumaya bint El; Cordova, Kyle E.; Rabadi, Ghaith; Abu Elhaija, Wejdan (Frontiers in Sustainability, 2021)
Higher education in Jordan has been tied closely to the state-building process in the century since the modern Hashemite state’s foundation in 1921, with its explicit purpose being to educate and train high volumes of students who are competent and capable to serve as contributors to the state’s development. Though this purpose has largely been successful to date, it is becoming increasingly clear that more is needed than simply issuing degrees. In an increasingly globalized world, it is necessary to educate those who can contribute to future research arenas and labor markets over which a single state has limited control. Within this perspective, we detail the evolved societal position that higher education institutions in Jordan occupy and how that position has made such institutions a liability in the nation’s continued sustainable development. Specifically, we outline the unsustainability of impersonal, inefficient and ineffective infrastructure, centralization of policies and academic practices, lack of autonomy and/or self-governance, considerable financial dependence on the state, and a general hesitation for higher education institutions to seek boldly societal and economic impact beyond the simple production of graduates. To counter this unsustainability, we propose a three-pronged approach that can help catalyze the re-imagining of Jordan’s higher education institutions so that they become maximally effective contributors to the state’s future sustainable development. Our proposed approach is based on (i) internally decentralizing higher education institutions to enable greater autonomy and academic freedom, (ii) re-purposing these institutions to become more student-centric, and (iii) embracing diversity and academic community recognition.